HEAVY METAL BIOACCUMULATION IN DUCKS AND POSSIBLE RISKS TO HUMAN HEALTH - R Susanti; Karima Widiyastuti (BIOTROPIA, 2022)
Meat is part of duck carcass mostly consumed by humans compared to other parts. This study aimed to analyze the heavy metal bioaccumulation factor (BAF) of duck meat and its possible risks to human health. A total of 25 duck samples with their drinking water and feed were taken from five intensive duck farms in Central Java Province, i.e., Semarang (A), Temanggung (B), Magelang (C), Pati (D) and Salatiga (E). Heavy metals concentration (As, Cd, Hg, and Pb) were measured following the ICP-OES method. Heavy metals concentration data obtained were then compared with the quality standard. The BAF value was calculated and the risks to human health were assessed. Our study found that drinking water provided for ducks in all farms contained heavy metals (As, Cd, Hg, and Pb) concentrations exceeding the quality standards. Hg concentration of 0.089 - 5.01 ppm in duck feed exceeded the quality standard. Concentrations of Cd (0.0713 - 0.075 ppm) and Hg (3.1 - 4.84 ppm) in duck meat exceeded the quality standard. The average of BAFduck meat values was in the range of 0.443 - 0.955. The EDI value of heavy metals (As, Cd, Hg, and Pb) for adults and children through consumption of duck meat in the Central Java region was lower than RfD. This study showed that the health risk parameters (EDI, HQ, and HI) were within safe limits. Exposure to heavy metals through duck meat consumption both in adults and children was unlikely to cause adverse health effects.